PRODUCTION OF ANGULAR VELOCITY GAUGE BASED ON FLUXGATE SENSOR AS MEDIA OF PHYSICS - ANWAR (NIM: 20207044), ZUL
Production of angular velocity gauge can be designed by using the principles of the magnet flux generated by the magnet fluxgate sensor, the design of sensor elements consists of the double secondary coil (pick-up) and excitation coil with 10 layers core layer which is input into the cavity isolative. Primary coil will generate internal magnetic fields that acts as reference magnetic fields, while the secondary coil acts to measure the external magnetic fields (sensing) so that the fluxgate sensor sensitivity is determined by the design of the secondary coil. Magnetic fields in the secondary coil will be zero when no external magnetic fields, otherwise the external magnetic fields will be not zero. Fluxgate magnetic sensor works based on the principles of second harmonics, the intensity of magnetic fields equal to the output voltage on the sensor.